EFEKTIVITAS TEKNIK WORD FLOW GAME TERHADAP KEMAMPUAN MENULIS KALIMAT BAHASA JEPANG PADA SISWA KELAS XI (SMA NEGERI 14 BEKASI TAHUN AJARAN 2018/2019) - Annuria Yustya Rahma; Retno Utari (Prosiding Seminar Nasional Berseri, 2020)
This research uses quasi-experimental quantitative research methods semu (Quasi Experiment Design). The population of this study was all students of class XI of SMA NEGERI 14 BEKASI in the academic year 2018/2019. The sample in this study was taken from class XI MIA 6 SMA NEGERI 14 BEKASI in the 2018/2019 school year, totaling 34 students. Based on the results of data processing, class XI MIA 6 obtained the number of pretest scores of 2574 with an average value of 75.71, the highest value of 86 and the lowest value of 62. At the total posttest score of 2888.5 with an average value of 84.95, the highest value of 98.0 and the lowest value of 64.5. Sig. (2-tailed) of 0,000 <0.05. Normalized Gain Value 10.05. The results of this study to improve students' ability to write Japanese sentences using the Word Flow Game technique are effective. Based on the results of the questionnaire, the Word Flow Game technique is that students become more enthusiastic, able to follow the learning of writing Japanese sentences well and can improve students' ability to write Japanese sentences and be interesting.